Rank criteria for the controllability of a boundary-value problem for a linear system of integro-differential equations with pulse influence - Akhmetov, M. U.; Seilova, R. D. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We determine necessary and sufficient conditions for the solvability of boundary-value problems for a linear system of integro-differential equations with pulse influence. We prove theorems on the existence and integral representation of solutions of linear second order integral-sum Volterra equations and linear systems of integro-differential equations with pulse influence at fixed times.